The Obtaining of Window Function Having Useful Spectral Parameters by Helping of Genetic Algorithm - Kaya, Turgay; Ince, Melih Cevdet (Elsevier Science Bv, 2013)
In this study, the design of useful window function containing together good properties of Kaiser and Ultraspherical windows preferred at many areas was implemented with helping of Genetic Algorithm (GA). Kaiser window has been used at many areas because of the fact that it has good characteristic specification such as mainlobe width and the ripple ratio for various applications but Kaiser Window having two parameters cannot control the sidelobe roll-off ratio. The ultraspherical window having three independent parameters has better sidelobe roll-off ratio than other windows in literature. At work, the coefficients of a new window function that has side-lobe roll-off ratio characteristic of ultraspherical window and Kaiser window's main-lobe width and ripple ratio were obtained by helping of GA. The obtained results from the improved method show better mainlobe width, ripple ratio and side-lobe roll-off ratio characteristic than other windows in literature. (C) 2013 The Authors. Published by Elsevier Ltd.
2nd World Conference on Educational Technology Researches (WCETR) -- JUN 27-29, 2012 -- Near E Univ, Nicosia, CYPRUS
Keywords: Window funciton; Ultraspherical window; Kaiser window; Exponantial window; Genetic Algorithm (GA)